A Wavelet-Based Multiresolution Reconstruction Method for Fluorescent Molecular Tomography - Wei Zou; Jiajun Wang; Kongpei Wu; David Dagan Feng (International Journal of Biomedical Imaging)
Image reconstruction of fluorescent molecular tomography (FMT) often involves repeatedly solving large-dimensional matrix equations, which are computationally expensive, especially for the case where there are large deviations in the optical properties between the target and the reference medium. In this paper, a wavelet-based multiresolution reconstruction approach is proposed for the FMT reconstruction in combination with a parallel forward computing strategy, in which both the forward and the inverse problems of FMT are solved in the wavelet domain. Simulation results demonstrate that the proposed approach can significantly speed up the reconstruction process and improve the image quality of FMT.